2009
DOI: 10.1160/th08-08-0558
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of urokinase receptor function and pericellular proteolysis by the integrin α5β1

Abstract: SummaryInteractions between the uPA receptor (uPAR) and various integrins, including α 5 β 1 , are known to modulate integrin-dependent cell adhesion, and we have shown that the integrin-associated tetraspanin protein CD82 down-regulates uPAR-dependent plasminogen activation by affecting α 5 β 1 cellular localisation. Here we have investigated whether overexpression of α 5 β 1 directly affects uPAR-dependent pericellular proteolysis. CHO cells overexpressing α 5 β 1 were found to activate plasminogen at a rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Our previous studies using both unbiased and biased approaches demonstrated that ATN-658 inhibits integrin signaling in vitro and in vivo as well as co-localization of α5β1 and uPAR [22], [27]. Our data suggest that the effects of ATN-658 on perturbing the uPAR-α5β1 interaction is indirect and direct binding of uPAR to integrin α5β1 or any other integrin using purified components has not been demonstrated [57], suggesting that these interactions require multiple components present at the cell surface. The existence of a signalosome containing uPAR has been postulated by D'Allessio and Blasi [58] and the data obtained to date supports the hypothesis that ATN-658 disrupts the signalosome leading to global effects on integrin signaling and inhibition of tumor progression (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Our previous studies using both unbiased and biased approaches demonstrated that ATN-658 inhibits integrin signaling in vitro and in vivo as well as co-localization of α5β1 and uPAR [22], [27]. Our data suggest that the effects of ATN-658 on perturbing the uPAR-α5β1 interaction is indirect and direct binding of uPAR to integrin α5β1 or any other integrin using purified components has not been demonstrated [57], suggesting that these interactions require multiple components present at the cell surface. The existence of a signalosome containing uPAR has been postulated by D'Allessio and Blasi [58] and the data obtained to date supports the hypothesis that ATN-658 disrupts the signalosome leading to global effects on integrin signaling and inhibition of tumor progression (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…When necessary these cells were differentiated by culturing in Medium 231 supplemented with 1% fetal bovine serum and heparin (30 g/ml) for 7 days. ␣5CHO (clone 17) and B2CHO cell lines were as previously detailed (29) and HT1080 were obtained from ATCC. These cells were maintained in Dulbecco's modified Eagle's medium (DMEM), supplemented with 10% (v/v) fetal calf serum, and 0.1 mM nonessential amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…Integrins link ECM to the actin cytoskeleton through FAK/ILK/SFK/Rho proteins pathway providing the traction necessary for cell motility (Geiger et al, 2001). Integrins regulate the localization and the activity of urokinase-type plasminogen activator (uPA)/uPA receptor (Ghosh et al, 2000; Wei et al, 2007; Bass and Ellis, 2009) and matrix metalloproteinases (MMPs; Lamar et al, 2008; Morozevich et al, 2009) therefore controlling ECM remodeling and the invasive process.…”
Section: Integrins In Gliomamentioning
confidence: 99%